Application of infrared spectroscopic analysis for quantification of free fatty acid content at palm oil mills - Nizam, A. F. A.; Azri, M. E. M.; Mior Ahmad Khushairi, Mohd Zahari; Mohd Sabri, Mahmud (IOP Publishing, 2020)
High free fatty acid (FFA) content results in low palm oil yield in refinery and 5 wt% are the limit for crude palm oil acceptance. Common method of the FFA quantification in the mills is titration. The intent of this study was to determine the FFA content in extracted palm oil by using Fourier transform infrared (FTIR) spectroscopy coupled with AOCS titration method for verification. The oil extractions took place on days 1, 5, 8, 12 and 15. The fruitlets were initially washed and autoclaved. By separating the kernel, the mesocarp was heated and pressed. After centrifugation, the oil from the top layer of extract was further analyzed. In this study, % transmittance of FFA had been measured at carboxyl band, C=O between 1730 and 1700 cm−1. The stretch of carboxyl band denotes that the FFA had proportionally increased with time. The FFA content of the samples increased in sigmoidal pattern with critical rise after day 8, reaching 15 wt% equilibrium states after 15 days. A calibration model was developed via linear regression and R2 of 0.979 indicating the results were significant.